2015
DOI: 10.3748/wjg.v21.i2.609
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative endoscopic retrograde cholangio-pancreatography: A useful tool in the hands of the hepatobiliary surgeon

Abstract: The hepatobiliary surgeon should be trained on ERCP as the third hand to expand his field of therapeutic options.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 36 publications
1
8
0
2
Order By: Relevance
“…Multivariate analysis revealed that young patients aged <35 years old, a CBD diameter >10 mm, and the number of pancreatic cannulations were independent risk factors for the development of PEP. 19 In the current study, PEP was noted significantly more in the ERCP group than it was in the conservative group. In all cases, pancreatitis was self-limiting by conservative treatment.…”
Section: Discussionsupporting
confidence: 39%
See 1 more Smart Citation
“…Multivariate analysis revealed that young patients aged <35 years old, a CBD diameter >10 mm, and the number of pancreatic cannulations were independent risk factors for the development of PEP. 19 In the current study, PEP was noted significantly more in the ERCP group than it was in the conservative group. In all cases, pancreatitis was self-limiting by conservative treatment.…”
Section: Discussionsupporting
confidence: 39%
“…18 Even with strict selection criteria, >10% of pre-operative ERCP are normal, and the possibility of occurrence of post-ERCP pancreatitis varies between 1% and 13.5%. 19 Unnecessary pre-ERCP can be avoided in many cases by managing CBDS with conservative treatment, which is effective in most of cases. This conservative management avoids the risks inherent in ERCP and unnecessary preoperative ERCP.…”
Section: Discussionmentioning
confidence: 99%
“…Rábago describe para la laparoendoscopía una tasa deéxito entre 69,2 % y 100 % con un promedio de 92,3 %. Una duración media de 35 minutos para la CPRE+EE intraoperatoria y duración media de la cirugía de 104 minutos, con rangos de 75-200 minutos (EL NAKEEB, A. et al, 2015). La tasa media de conversión a cirugía abierta 4,7 %, morbilidad del 5,1 % (0 % -19 %) y una mortalidad extremadamente rara 0,37 % (RÁBAGO et al, 2011).…”
Section: Discussionunclassified
“…En la práctica quirúrgica actual, la exploración laparoscópi-ca de la vía biliar y la incorporación de procedimientos endoscópicos intraoperatorias en el diagnóstico y tratamiento de cálculos en el colédoco, mantienen las ventajas de la cirugía mínimamente invasiva, pero requieren recursos técni-cos, experiencia y adaptación del procedimiento a la cirugía o mínimamente invasiva, en donde el cirujano hepatobiliar, posea la competencia de resolución endoscópica (El NAKEEB et al, 2015;WEI et al,2003).…”
Section: Introductionunclassified
“…Endoscopic retrograde cholangiopancreatography (ERCP) is a useful tool for diagnosis and treatment of obstructive jaundice [1][2][3][4]. ERCP needs patient cooperation and adequate sedation.…”
Section: Introductionmentioning
confidence: 99%